MicroRNA Dysregulation and Steroid Hormone Receptor Expression in Uterine Tissues of Rats with Endometriosis during the Implantation Window - Han Cai; Xin-Xin Zhu; Zhan-Fei Li; Ya-Pei Zhu; Jing-He Lang (Chinese Medical Journal, 2018)
Background: Estrogen receptor (ER) and progesterone receptor (PR) are involved in endometriosis, but the involvement of microRNAs (miRNAs) is unknown. The aim of the study was to explore the correlation between miRNA and ER/PR in uterine tissues of rats with endometriosis during the implantation window. Methods: Twenty female Sprague-Dawley rats were randomized in three groups: endometriosis (n = 7), fat tissue control (n = 6), and normal (n = 7) groups. The female rats were mated and sacrificed on day 5 (implantation). Uterine tissues were obtained for hematoxylin-eosin staining, immunohistochemistry, and miRNA expression. Reverse transcription polymerase chain reaction (RT-PCR) was used to validate the expression of rno-miR-29c-3p, rno-miR-34c-5p, rno-miR-141-5p, rno-miR-24-1-5p, and rno-miR-490-5p. Results: The 475 miRNAs were found to differentially express between the endometriosis and normal control groups, with 127 being upregulated and 348 being downregulated. Expression of five miRNAs (rno-miR-29c-3p, rno-miR-34c-5p, rno-miR-141-5p, rno-miR-24-1-5p, and rno-miR-490-5p) were validated by RT-PCR and found to be differentially expressed among the three groups. Expression of ER and PR proteins (immunohistochemistry) in the glandular epithelium and endometrial stroma was significantly different among the three groups (all P < 0.05). Five miRNAs were involved in pathways probably taking part in implantation and fertility. Conclusions: The results suggested that miRNAs, ER, and PR could play important roles in the embryo implantation period of rats with endometriosis. These miRNAs might play a role in endometrial receptivity in endometriosis.